Fifty years of capacity building: Taking stock and moving research forward. (5th August 2022) - Kacou, Kablan P.; Ika, Lavagnon A.; Munro, Lauchlan T.
Abstract: This paper assesses the literature on "capacity building" through a systematic literature review. Taking concepts as the ontological building blocks of theories, we ask: what is known about the evolution of capacity building as a concept and what can that history tell us about its strengths and weaknesses? To this end, we dig into the conceptual and theoretical underpinnings of capacity building. Through this Foucauldian "archaeological description", we show that capacity building discourse has evolved dialectically, with each new concept emerging to address the failings of earlier concepts. The paper suggests the "new pragmatism" as a theoretical framework to guide a more rigorous and relevant theory and practice of capacity building especially for public administration. Rooted in sensitivity to context and methodological pluralism, the new pragmatism embraces complexity, delivers "best‐fit" rather than "best practice" solutions, and involves researchers and practitioners in decolonial knowledge co‐creation to tackle capacity building challenges.